2004
DOI: 10.1111/j.1365-2222.2004.1931.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mycobacterium tuberculosis chaperonins on bronchial eosinophilia and hyper‐responsiveness in a murine model of allergic inflammation

Abstract: These data show that bacterial Cpns can suppress eosinophil recruitment and bronchial hyper-responsiveness in a murine model of allergic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 57 publications
6
35
0
Order By: Relevance
“…Analysis of a transposon mutant library of Mycobacterium avium revealed a number of genes (not including cpn60.1) that impair biofilm formation (42). The virtually identical Cpn60.2 proteins from M. tuberculosis and M. leprae have very different anti-inflammatory actions in mice (30,31), and in general, different Cpn60 proteins exhibit a bewildering variety of activities (4,32). Given these findings, it is not surprising that M. tuberculosis Cpn60.1 does not behave identically to the M. smegmatis homologue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of a transposon mutant library of Mycobacterium avium revealed a number of genes (not including cpn60.1) that impair biofilm formation (42). The virtually identical Cpn60.2 proteins from M. tuberculosis and M. leprae have very different anti-inflammatory actions in mice (30,31), and in general, different Cpn60 proteins exhibit a bewildering variety of activities (4,32). Given these findings, it is not surprising that M. tuberculosis Cpn60.1 does not behave identically to the M. smegmatis homologue.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis Cpn60.1 is a more potent activator of human monocyte cytokine synthesis than is Cpn60.2 (12). Paradoxically, it has also been reported that acute administration of M. tuberculosis Cpn60.1 (31) or Mycobacterium leprae Cpn60.2 (30), but not M. tuberculosis Cpn60.2 (31), can inhibit experimental allergic asthma in the mouse, suggesting that these proteins can also act as anti-inflammatory signals. This raises the question of the role played by any Cpn60 protein released by mycobacteria.…”
mentioning
confidence: 99%
“…The host-inflammatory response is driven by pro-inflammatory mediators including the cytokines IL-1β, TNF-α and IL-8 (CXCL8), upregulation of adhesion molecules and proteolytic enzymes leading to the migration of leukocytes to the site of inflammation for TH1 responses [3]. Whilst for TH2 responses in the asthmatic lung activation of integrins on circulating eosinophils followed by tethering and rolling on bronchial endothelial cells [4] with increases in IL-4 and IL-5 leading to further activation and subsequent transmigration [5]. To aid in the resolution of this response a number of endogenous modulators of inflammation are produced including annexin 1 [6], galectin [7], lipoxins [8] and melanocortins [9,10] and these have been shown to inhibit leukocyte trafficking and help prevent tissue damage.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Note that the mycobacteria generally code for two or three Cpn60 proteins (106). However, in both of these studies (150,152) other bacterial Cpn60 proteins, including the M. tuberculosis Cpn60.2 molecule, failed to show anti-inflammatory activity. This is surprising given that the M. tuberculosis and M. leprae Cpn60.2 proteins exhibit 95% sequence identity at the amino acid level.…”
Section: Bacterial Molecular Chaperones As Virulence Factorsmentioning
confidence: 92%
“…However, certain bacterial molecular chaperones have an apparent anti-inflammatory action. Thus, administering the recombinant Cpn60.1 protein of M. tuberculosis inhibits experimental asthma, an inflammatory lung condition, in the mouse (152). The M. leprae Cpn60.2 protein is also a potent inhibitor of this experimental disease (150).…”
Section: Bacterial Molecular Chaperones As Virulence Factorsmentioning
confidence: 99%